2021
DOI: 10.5545/sv-jme.2021.7106
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Internal Roller Burnishing Process for Energy Reduction and Surface Properties

Abstract: Improving the surface quality after burnishing operation has been the subject of various published investigations. Unfortunately, the trade-off analysis between the energy consumption and surface characteristics of the internal burnishing has been not addressed due to the expensive cost and huge efforts required. The objective of the present work is to optimize burnishing factors, including the spindle speed, burnishing feed, depth of penetration, and the number of rollers for minimizing the energy consumed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Figure 10 (b) shows the relationship between surface roughness average and feed rate value subjected to the spring tool. However, previous studies showed that the surface roughness was decreased as the feed rate increased until it reaches a certain value then it begins to be increased again [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Furthermore, in this study increasing the feed rate is correlated with an increase in surface roughness [21].…”
Section: Burnishing Feed Ratementioning
confidence: 60%
See 1 more Smart Citation
“…Figure 10 (b) shows the relationship between surface roughness average and feed rate value subjected to the spring tool. However, previous studies showed that the surface roughness was decreased as the feed rate increased until it reaches a certain value then it begins to be increased again [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Furthermore, in this study increasing the feed rate is correlated with an increase in surface roughness [21].…”
Section: Burnishing Feed Ratementioning
confidence: 60%
“…As manufacturing tolerances progressively tighten to meet precision requirements in applications involving fluid sealing, coefficient of friction control, and miniature clearances, understanding how surface shaping methods like burnishing sculpt very near-surface geometry becomes imperative [7,8]. Previous research has also identified opportunities to optimize process parameters to reduce energy consumption during surface treatment while enhancing surface quality [9]. For instance, it has been observed that surface roughness decreases with increasing burnishing speed, reaching a minimum value before rising again at higher speeds [10].…”
Section: Introductionmentioning
confidence: 99%
“…The outcome demonstrates a 90% reduction in surface roughness and a 41% improvement in microhardness. Nguyen, T. T. et al [3] innovated the goals in terms of Internal Roller Burnishing parameters by utilizing an adaptive neurobased fuzzy inference system (ANFIS). the result of the optimization process.…”
Section: 𝐾 𝑈 = 𝐹…8mentioning
confidence: 99%
“…The energy efficiency of the internal burnishing was enhanced by 7.0%, while the noise emission and Rs were decreased by 2.2%, and 25.0% [12]. Nguyen and Le revealed that the energy consumption and Rs of the external burnishing were reduced by 33.0% and 16.0%, respectively [13]. Nguyen et al stated that the total energy, mean roughness, and roundness of the MQL-assisted internal burnishing were reduced by 12.0%, 14.0%, and 43.0%, respectively [14].…”
Section: Introductionmentioning
confidence: 99%